Water Balance in Oil Palm Plantation with Ridge Terrace and Nephrolepis biserrata as Cover Crop - Ariyanti, Mira; Yahya, Sudirman; Murtilaksono, Kukuh; Suwarto, Suwarto; Siregar, Hasril H. (Department of Agronomy and Horticulture, IPB University, 2016)
The existence of oil palm plantations as a possible cause of drought in the surrounding areas in Indonesia is a critical issue. Therefore, information related to the effects of oil palm plantations on the surrounding environment in terms of soil water content (SWC) availability is needed. Soil and water conservation techniques in the form of ridge terracing and cover crops, such as Nephrolepis biserrata, can be expected to potentially improve soil water reserves, especially in the dry-season, by accumulating water in the rainy season. This study aimed to study the effects of N. biserrata as cover crop, together with the potential effects of ridge terraces, on the water balance in mature oil palm plantations. The research was conducted in mature oil palm plantations, Afdeling III block 375 (planted in 1996) and block 415 (planted in 2005), Rejosari Unit, PT Perkebunan Nusantara (PTPN) VII in Natar District, South Lampung Regency, Indonesia, from August 2014 to January 2015. The research was based on of setting up 15 m x 20 m experimental plots with the following treatments: (i) without ridge terraces and without N. biserrata (G0T0); (ii) without ridge terraces but with N. biserrata (G0T1); (iii) with ridge terraces but without N. biserrata (G1T0); (iv) with ridge terraces and with N. biserrata (G1T1). Hydrology parameter data were collected for each treatment plot; water balance was calculated using a water balance equation. The results showed that the use of the cover crop N. biserrata in combination with ridge terraces helped improving SWC reserves by approximately 71% and 12%, respectively. The use of N. biserrata as a cover crop reduced the rate of water loss by percolation and run-off, by approximately 36% and 80%, respectively, in an area where the annual rainfall is above 2,400 mm per year. The presence of N. biserrata shortened the period of SWC deﬁcit by extending the period of a water surplus by 70 days when compared with ridge terracing alone (which reduced the period of SWC by 50 days).